Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1172/jci113401
|View full text |Cite
|
Sign up to set email alerts
|

Thymus in myasthenia gravis. Isolation of T-lymphocyte lines specific for the nicotinic acetylcholine receptor from thymuses of myasthenic patients.

Abstract: The thymus is believed to play a central role in the pathogenesis of Myasthenia gravis (MG). According to a previous hypothesis, MG is initiated within the thymus by immunogenic presentation of locally produced nicotinic acetylcholine receptor (AChR) to potentially autoimmune T cells. Data of 10 consecutive MG patients demonstrate two critical features of MG thymuses that support the concept of intrathymic activation of autoreactive, AChR-specific lymphocytes. Morphologically, the thymuses showed lympho-follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
6

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(74 citation statements)
references
References 42 publications
(16 reference statements)
2
66
0
6
Order By: Relevance
“…The disease is controlled by AChR-specific T cells found in the thymus and peripheral blood of MG patients. The presence of the pathogenic T cells within the myasthenic thymus suggests that the disease is initiated in the pathologically transformed thymus (20,21). Corticosteroids, especially prednisolone (pred), are the treatment of choice for many MG patients (22), because they seem to be effective in inducing remission in a large cohort of patients.…”
Section: Prednisolone Treatment Induces Tolerogenic Dendritic Cells Amentioning
confidence: 99%
“…The disease is controlled by AChR-specific T cells found in the thymus and peripheral blood of MG patients. The presence of the pathogenic T cells within the myasthenic thymus suggests that the disease is initiated in the pathologically transformed thymus (20,21). Corticosteroids, especially prednisolone (pred), are the treatment of choice for many MG patients (22), because they seem to be effective in inducing remission in a large cohort of patients.…”
Section: Prednisolone Treatment Induces Tolerogenic Dendritic Cells Amentioning
confidence: 99%
“…These thymic abnormalities are correlated with the antiAChR Ab titer which decreases after thymectomy (7). The hyperplastic thymus includes all the components of the anti-AChR response: the AChR (8), B cells producing anti-AChR Abs (9), and anti-AChR autoreactive T cells (10). Thus, the thymus plays a pivotal role in the pathogenesis of SP MG and an understanding of the mechanisms leading to ectopic GC formation is expected to shed light on the pathogenesis of this disease.…”
Section: A Cquired Myasthenia Gravis (Mg)mentioning
confidence: 99%
“…24 The presence of germinal centers and maturation of B cells in the thymus support the idea of presentation of autoantigens and development of autoreactive cells that escape the mechanisms of negative selection, although it is currently unknown whether the pathology originates in the thymus or if the thymus is filled with autoreactive T cells that have re-entered the thymus after being activated in the periphery. 10 As a paraneoplastic syndrome in thymomas, about 40% of patients have MG and are positive for anti-AChR autoantibodies, and, vice versa, thymic tumors are found in about 10% of the MG patients, usually between 40 and 60 years of age. Thymic tumors associated with MG are predominantly thymomas of the cortical, mixed or medullary subtype, or welldifferentiated thymic carcinoma, and it is suspected that the etiology of the MG-associated thymoma is different from that of MG-associated TFH.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 This thymitis or thymic lymphofollicular hyperplasia (TFH) is characterized by the presence of germinal centers within the thymic medulla, 6,7 which support expansion and affinity maturation of B-cell clones and facilitate the production and export of AChR-specific antibodies. 8 AChR-specific T cells are found in the myasthenic thymus, 9 and T-cell lines could be established from thymi from myasthenia patients, 10 suggesting that autoantigen-specific T cells mature in the pathologically transformed thymus and influence the humoral immune response in the periphery. 11 To test whether PRSS16 is altered in the thymus of MG patients, we investigated the expression of this protease in thymi from healthy controls and in thymic samples from patients with MG. We found that PRSS16 is alternatively spliced in the human thymus.…”
Section: Introductionmentioning
confidence: 99%